The mythopoetics role in the formation of the chronotope of L. Andreev’s play "Anatema" - Сухоруков, Віктор Анатолійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The analysis of poetics of L. Andreev’s play “Anathema” showed that productive research of this drama is possible only in the wide context of works, that not only form the dramatical cycle “The God, devil and men” but a series of L. Andreev’s short stories and stories, where the author interprets the Bible history of Jove (“ The life of Vassilyj Fivyskiy”, “The sun of men”) and the Gospel history of Christ and Judas (“Ben-Jovit”, “Judas Iskariot”) under different points of view. First of all we have in mind the role of ironical, nonortodoxal neomythologism in the drama “Anathema”. We also note that Andreev in the play “Anathema” advatageble used powerful philosophical and mythosymbolical potential not opened, like in drams “The Life of Man” and “Blach masks”, but closed artistic spaces – of desert and especially of sea, that becomes ideologically – artistical center of dram. Herewith the writer created volumetrical, manyleveled chronotop, where the town, devided by the gates from one side and the sea from another side become not only the most symbolically important space plans, but plotallyfounding pales. The study showed that the important role in this work play modernistic principles of representation of world and person as neomythologism, intertextuality, motifity, dominating of symbolical types and characters, irony, grotesque. The article “Life of a Man” demonstrated that the “new drama” by L. Andreev has been promoting such a type of conflict, which shows the way of collision, where the Wall resists the Man in its various forms. In the "new myth" of the writer, it turned to Rock (Someone in Gray). Therefore, the basis of the drama "Life of Man" was based on the conflict "Man and Rock", embodied in adequate artistic forms. The study of L. Andreev’s drama’s chronotop in various periods of his work, along with variability, demonstrates his apparent conceptual uniformity. The local framework, where he transfers the action in this play (the room where the Life of Man flows) is an invariant of special variation of locuses of early dramas and play of “panpsihe”. Apparently, both in prose, and in dramaturgy of the writer there was no evolution, the accents in the author’s concept only changed and the appropriate art means and image forms merely varied. Already in the first dramas all was put that only came to light, deepened and became more obvious.